Joint Beamforming Design and Power Minimization for Friendly Jamming Relaying Hybrid RF/VLC Systems - Ai-Khori, Jaber; Nauryzbayev, Galymzhan; Abdallah, Mohamed M.; Hamdi, Mounir (Institute of Electrical and Electronics Engineers, 2019)
In this paper, we study physical layer security (PLS) aspects of a hybrid radio frequency (RF)/visible light communication (VLC) system with multiple decode-and-forward relaying nodes equipped with friendly jamming capabilities. We first propose a novel joint relay-jammer selection algorithm to enhance the secrecy performance of the network. Next, we obtain beamforming vectors and the minimal power values, which satisfy the required secrecy threshold. Our simulation results show that the proposed hybrid RF/VLC scheme obtains higher secrecy capacity compared to the standalone VLC and RF technologies. Finally, we proved the proposed technique to be an eavesdropping-resilient PLS solution.
https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=8668776
Keywords: Beamforming; BF; optimization; physical layer security; PLS; radio frequency; relaying; RF; secrecy; visible light communication; VLC